Anticoagulation Failure: Deep Vein Thrombosis Despite Severe Coagulopathy in a Patient with Mechanical Heart Valves - Anak Agung Sagung Karinia Jaya; I Made Agus Endra Permana (Open Access Indonesian Journal of Medical Reviews, 2025)
The management of patients with mechanical heart valves on chronic warfarin therapy is a delicate balance between preventing thromboembolism and avoiding hemorrhage. The emergence of an acute thrombotic event despite a critically elevated International Normalized Ratio (INR) represents a profound clinical paradox and a significant management dilemma. This report details such a case, offering a deep exploration of the underlying pathophysiology. A 34-year-old female with dual mechanical heart valves for severe rheumatic heart disease, maintained on a variable-dose warfarin regimen, presented with acute deep vein thrombosis (DVT) of the right lower limb. Her INR was critically elevated at 7.78. A detailed history revealed recent poor oral intake followed by inconsistent dietary changes, contributing to extreme INR lability. Diagnostic investigations confirmed a non-occlusive, distal DVT. The management strategy involved immediate cessation of warfarin without the administration of reversal agents, prioritizing the prevention of mechanical valve thrombosis. The INR was allowed to normalize gradually over 72 hours, with concurrent clinical improvement. Warfarin was cautiously re-initiated, and a long-term management plan focusing on intensive education and monitoring was established. In conclusion, this case demonstrates that a supratherapeutic INR does not confer absolute protection against venous thrombosis in patients with potent, underlying prothrombotic risk factors. The principles of Virchow's triad—particularly venous stasis from chronic heart failure and a persistent hypercoagulable state from prosthetic valves and systemic inflammation—can override the systemic anticoagulant effect measured by the INR. Management of this paradox requires a highly individualized, pathophysiology-driven strategy that carefully weighs the competing risks of hemorrhage, thrombus extension, and catastrophic valve thrombosis.